Research handbook on copyright law - Torremans, Paul, 1965-; Edward Elgar Publishing (Cheltenham : Edward Elgar Publishing, 2017)
This second edition has been completely rewritten to reflect recent changes and new trends that have emerged since the popular first edition was published. Copyright law has become a fast moving area, which is reflected in the wealth and diversity of research. This comprehensive Research Handbook is situated at the cutting edge of current copyright research, with each chapter written by a leading author in that particular field. The Research Handbook begins with an examination of fundamental questions such as the historical foundations of copyright, the basic concept of originality and the significant discussion on communication to the public. The contributors then focus on moral rights and the artist resale right. In-depth treatment of specialist topics is provided, including copyright contracts, collective management, issues surrounding streaming and sampling, cultural heritage, orphan works, search engines and the potential for a public policy exclusion. The Research Handbook provides global coverage while also considering specific jurisdictions and private international law. The Research Handbook on Copyright Law is a rich research tool that reflects the wealth and diversity of the ongoing research in copyright. It is essential reading for students and researchers in copyright and intellectual property law, as well as practitioners and policymakers.
Introduction -- 1. Walking the copyright tightrope / Ysolde Gendreau -- 2. Copyright history as book history: the law in multidisciplinary context / Myra J. Tawfik -- 3. Originality under EU copyright law / Irini A. Stamatoudi -- 4. When the Court of Justice of the European Union sets about defining exclusive rights: copyright quo vadis? / Paul Torremans -- 5. The right of "communication to the public" in the European Union / Fabienne Brison and Sari Depreeuw -- 6. The WIPO right of making available / Gaetano Dimita -- 7. Enforcing the EU communication to the public right in cases of ubiquitous infringement / Justin Koo -- 8. Invitation for a 'Europeanification' of moral rights / Marie-Christine Janssens -- 9. Can only compulsory collective management guarantee that an author actually receives his resale right? / Hendrik Vanhees -- 10. The remuneration of authors and performers in copyright contract law / Agnès Lucas-Schloetter ---11. Sampling of sound recordings in the United States and Germany: revival of a discussion on musical creativity / Bernd Justin Jütte -- 12. The borderless online user - carving up the market for online and streaming services / Thomas Riis and Jens Schovsbo -- 13. Private copying exception and payment of fair compensation. EU case-law / Gemma Minero -- 14. The ownership of rights on the works created within the universities and public research organizations: special features of Spanish law / Pilar Cámara Águila -- 15. Who owns the orphans? Property in digital cultural heritage assets / Uma Suthersanen -- 16. Copyright in works reproduced and published online by search engines / Ernesto Rengifo -- 17. Collective management and exclusive rights, friends or foes? / Sylvie Nérisson -- 18. Copyright and related rights: outlining a case for a european morality / public policy exclusion / Justine Pila ---19. Copyright, contemporary intangible cultural heritage and freedom of expression: mapping the terrain / Charlotte Waelde -- 20. Albanian copyright law and the challenges of the approximation with the legislation of the European Union / Blerina Mullisi -- 21. Copyright infringement in Vietnam: Recognising the reasons and suggested solutions / Nguyễn Hồ Bích Hằng -- 22. Can copyright law be transplanted? Vietnam's experiences with droit d'auteur between 1864 and 1975 / Tran Kien -- 23. Copyright jurisdiction under EU private international law / Paul Torremans -- Index.
Obsahuje bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: autorské právo; copyright; e-knihy online; e-books online